2012
DOI: 10.1186/1471-2369-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic kidney disease are at an elevated risk of dementia: A population-based cohort study in Taiwan

Abstract: BackgroundChronic kidney disease (CKD) is more prevalent in Taiwan than in most countries. This population-based cohort study evaluated the dementia risk associated with CKD.MethodsUsing claims data of 1,000,000 insured residents covered in the universal health insurance of Taiwan, we selected 37049 adults with CKD newly diagnosed from 2000–2006 as the CKD cohort. We also randomly selected 74098 persons free from CKD and other kidney diseases, frequency matched with age, sex and the date of CKD diagnosed. Inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 53 publications
4
37
1
1
Order By: Relevance
“…Renal disease is a major component of the CRS [51,52], and independently, renal disease is associated with diabetes, hypertension, and hyperlipidemia as occurs in the CRS. The progression of CRS-associated renal dysfunction to chronic kidney disease is linked to increases in oxidative stress, inflammation, chronic anemia, vascular calcification, and increased homocysteine, uric acid, and parathyroid hormone [53].…”
Section: Cardiac and Renal Contributions To DCmentioning
confidence: 99%
“…Renal disease is a major component of the CRS [51,52], and independently, renal disease is associated with diabetes, hypertension, and hyperlipidemia as occurs in the CRS. The progression of CRS-associated renal dysfunction to chronic kidney disease is linked to increases in oxidative stress, inflammation, chronic anemia, vascular calcification, and increased homocysteine, uric acid, and parathyroid hormone [53].…”
Section: Cardiac and Renal Contributions To DCmentioning
confidence: 99%
“…All comorbidities, including pyogenic liver abscess, were also diagnosed according to ICD-9 codes, the accuracy of which has been validated in previous studies [40][41][42][43][44][45][46][47][48][49][50][51][52]. Finally, we had a large sample, a sound study design, and appropriate statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of cross-sectional and longitudinal studies comprising 54,779 participants, suggested an association of cognitive decline in CKD patients compared with patients without CKD (OR 1.65, 95% confidence interval (CI) 1.32-2.05; p<0.001; OR 1.39, 95% CI 1.15¬¬-1.68; p<0.001, respectively) [73]. In Taiwan that has the highest prevalence rate of ESRD worldwide, the incidence of dementia was higher in the CKD cohort than in the non-CKD cohort (9.30 vs. 5.55 per 1,000 person-years), with an overall hazard ratio (HR) of 1.41 (95% confidence interval (CI), 1.32-1.50), controlling for sex, age, comorbidities, and medications [74]. Therefore, CKD is a significant and independent somatic risk factor in the development of cognitive decline.…”
Section: Geriatric Syndromes In Ckd Patientsmentioning
confidence: 99%